Fournier’s gangrene – a clinical case report - Adamczyk, Katarzyna; Wojcik, Rafal; Adamczyk, Dorota; Kozak, Krzysztof; Jasińska, Ewa; Piasecka-Twaróg, Małgorzata (Journal of Education, Health and Sport, 2018)
Fournier’s gangrene is an acute, rapidly progressive, necrotizing infection of the skin and subcutaneous tissues surrounding the genitals and perineum. Necrotizing fasciitis of the genital area is a rare disease entity. Although it concerns mostly males, can also occur in females and adolescents. In this syndrome, bacteria produce gases which accumulate in the infected tissue. The damage may also comprise tissue of the penis and scrotum. The infection is caused by aerobic and anaerobic bacteria. Usually the Fournier’s gangrene is caused by Staphylococci, Streptococci and Enteric bacteria. Bacterial infection can accompany the fungal infection. The high mortality rate is associated with bacterial contagion of the skin, fat, fascia and blood vessels. Harmful enzymes, produced by micro-organisms, induce numerous blood clots. They can lead to ischemia, which contribute to the development of necrosis. Fournier’s syndrome is a disease with a high mortality rate. Immunodeficiency, diabetes and chronic alcohol abuse favor the development of gangrene. Abrasion, burn or surgery complication may be the route of infection for microorganisms. Clinical symptoms appear within few days. Diagnostic process is based on the clinical picture. It is crucial to start treatment as soon as possible. Delay of the wide spectral intravenous antibiotic therapy and surgical removal of the necrotic tissue may result in death of the patient.